Active Tasks to Change the Use of Class Time within an Outcomes Based Approach to Curriculum Design - Salter, Dr Diane; Pang, Dr Marco; Sharma, Dr Piyush (Journal of University Teaching and Learning Practice, 2009)
This paper describes how new roles for instructors and learners can be integrated into course design and delivery by rethinking course design as part of a process-based staff development program. The goal of incorporating online learning tasks was to engage students with course resources prior to class time through active learning. The staff development program guided faculty to consider ways to ‘rethink’ the use of student and teacher time to engage students in learning tasks to prepare for class time. In this way, students were able to use class time for active discussion rather than listening to a traditional lecture in the classroom. This paper reports on the overall results of this project and provides specific suggestions on how teachers can consider technology options within an outcomes-based approach to curriculum design.